2020
DOI: 10.3390/foods9020181
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the Anti-Inflammatory Effect of Mustard Kimchi on RAW 264.7 Macrophages by the Lactobacillus plantarum Fermentation-Mediated Generation of Phenolic Compound Derivatives

Abstract: Mustard leaf kimchi contains numerous functional compounds that have various health benefits. However, the underlying mechanisms of their anti-inflammatory effects are unclear. In this study, changes in the mustard leaf kimchi phenolics profile after fermentation with or without Lactobacillus plantarum were determined using liquid chromatography–mass spectrometry/mass spectrometry (LC–MS/MS). To correlate changes in phenolic profiles with anti-inflammatory activities of the fermentation extracts, lipopolysacch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 36 publications
2
2
0
Order By: Relevance
“…However, a substantive improvement and reduction in these parameters were observed after remedy with B. juncea in its both forms either as a prophylactic or as a treatment; however, the nanoforms have shown a greater significant effect on the elevated serum liver enzymes and the rehabilitation of the liver architecture as well. These outcomes go in line with Yang et al [ 31 ] and seem to be consistent with what recently announced by Khaled [ 32 ], Melrose [ 27 ] and Le et al [ 33 ] as they archived the amazing cell reinforcement and hepatoprotective properties of mustard against poisonousness instigated free radicals harm in the liver and furthermore with Walia et al [ 11 ] as he detailed ethanolic leaf concentrate of B. juncea could be a superior medication of decision as a hepatoprotective plant source. The free radicals scavenging effects of mustard extracts are most in all likelihood attributed to its better polyphenols and flavones contents.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, a substantive improvement and reduction in these parameters were observed after remedy with B. juncea in its both forms either as a prophylactic or as a treatment; however, the nanoforms have shown a greater significant effect on the elevated serum liver enzymes and the rehabilitation of the liver architecture as well. These outcomes go in line with Yang et al [ 31 ] and seem to be consistent with what recently announced by Khaled [ 32 ], Melrose [ 27 ] and Le et al [ 33 ] as they archived the amazing cell reinforcement and hepatoprotective properties of mustard against poisonousness instigated free radicals harm in the liver and furthermore with Walia et al [ 11 ] as he detailed ethanolic leaf concentrate of B. juncea could be a superior medication of decision as a hepatoprotective plant source. The free radicals scavenging effects of mustard extracts are most in all likelihood attributed to its better polyphenols and flavones contents.…”
Section: Discussionsupporting
confidence: 93%
“…However, these parameters were remodulated and downregulated by mustard extract treatment in both normal and its nano form either pre-or post TAA intoxication. These good responses may be supportive of Le et al [ 33 ] as they suggested the anti-inflammatory properties of the B. juncea spice/herb ( Figure 6 ).…”
Section: Discussionsupporting
confidence: 87%
“…Mustard has been found to be useful in the treatment of pneumonia, asthma, or cough and in relieving pain symptoms, such as headaches and neuralgia. Since fermentation with Lactobacillus Plantarum can enhance the anti-inflammatory activity of mustard leaves, mustard leaves fermented by this microorganism may be helpful in the treatment of inflammation [ 34 ]. The SARS-CoV-2 protein 3CLPro is essential for successful viral replication.…”
Section: Discussionmentioning
confidence: 99%
“…Although RE moderately inhibited S. aureus-induced IL-8 mRNA expression, both LP-RE and LR-RE more effectively inhibited S. aureus-induced IL-8 mRNA expression, suggesting that the bioconversioned RE has anti-inflammatory effects in human intestinal epithelial cells. In previous studies, the anti-inflammatory effect was caused by the increment of metabolites and enhanced bioaccessibility or bioavailability of phenolic compounds [16][17][18].…”
Section: Bioconversioned Re Inhibits S Aureus-induced Il-8 Expressionmentioning
confidence: 97%